Primary school teachers' awareness on dyslexia and management of students with dyslexia in Kuching division - Chai, Sylvia Hsieh Lin (Universiti Malaysia Sarawak, UNIMAS, 2009)
Primary school teachers play a significant role in the early identification of students with dyslexia, and their awareness on dyslexia would be of assistance in the management of students with dyslexia. This study aimed to find out the awareness on dyslexia and management of students with dyslexia, by the teachers from national primary schools (Sekolah Kebangsaan) with and without Program Pendidikan Khas Integrasi, in Kuching division. This study also sought to identify the number of teachers who had been trained in special education and the number of teachers who has experience in teaching students with dyslexia. This study utilised a survey approach using a set of questionnaire. The sample consisted of 143 teachers from seven selected national primary schools, of which four were without Program Pendidikan Khas Integrasi and three were with the programme, in Pejabat Pelajaran Gabungan (PPG) Kuching. Based on the findings, it was identified that there were twelve teachers who had been trained in Special Education; while only five teachers indicated having experience in teaching students with dyslexia. It was found that the teachers had basic awareness on dyslexia yet lackedthe awareness on specific symptoms of dyslexia which was crucial in early identification of students with dyslexia. Also, the teachers were found to know the procedure to be taken should they suspect having a student with dyslexia in their classroom. In addition, they stated that consultation support and access to information regarding the management of students with dyslexia were available for them. Nonetheless, the teachers were found lacking in the ability in making adaptations in teaching materials and assessment to suit the needs of students with dyslexia. This study had extended the empirical database on national primary school teachers’ awareness on dyslexia and the management of students with dyslexia in Kuching division. The primary school teachers needed more input on the specific symptoms of dyslexia in enabling them to contribute effectively in the early identification of students with dyslexia. Besides, they should be given guidance on the management of students with dyslexia in terms of adaptations of teaching materials and assessment in maximising the learning potentials of the students with dyslexia.